Breakdown of Water-in-Oil Emulsion on Pyrolysis Bio-Oil - Muhammad Rizky Zen; Susila Arita; Leily Nurul Komariah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
The pyrolysis bio-oil which has been studied by many researchers has typically contained a high amount of water, around 20-30%. In this research, the effective bio-oil purification using chemical demulsification method has been studied to reduce the amount of water by breaking down the water-in-oil emulsion on pyrolysis bio-oil. A various dosage of chemical demulsifier (100 ppm, 150 ppm, 200 ppm, and 250 ppm) has been added into the pyrolysis bio-oil and the water separation over time also been observed. The temperature of bio-oil (30, 40, 50, 60, and 70 °C) was also studied as a factor that could have a significant effect on the demulsification process of pyrolysis bio-oil. After the injection of 250 ppm of demulsifier at 30 °C, the water separation reached a maximum of 72% in 60 minutes and could reduce the water content from 25% to 8.5%. At the temperature of 60oC and 250 ppm of demulsifier, the water separation reached a maximum of 96% in 35 minutes, and successfully reduced the water content from 25% to 1.3%. Finally, it has been concluded that this bio-crude purification using chemical demulsification method could be applied to effectively reduce the amount of water from pyrolysis bio-oil product.